The Effect of Non-Interest Income on Bank Profitability and Risk: Evidence from Turkey - Nilgün Acar Balaylar; Turan Karımlı; Ahsen Emir Bulut (Revista Galega de Economía)
There are three purposes of this article, the first of which is to investigate the impact of non-interest income (NNII) on the profitability of banks assessed by both return on assets (ROA) and return on equity (ROE). The second one is to investigate the impact of NNII on risk, assessed by the volatility of return on assets (SdROA) and the volatility of return on equity (SdROE). The final one is to analyze the impact of the COVID-19 pandemic on bank profitability and risk. To achieve the above, the dynamic panel technique, a two-step GMM estimator, was used with the data of 25 deposit banks operating uninterruptedly from 2002 to 2021. The empirical results show that the NNII was positive and significantly correlated with ROA and ROE. The effect of NNII on the risk level appears to be negative and significantly related. In addition, during the COVID-19 period, it was determined that profitability decreased and risk increased. This shows that NNII is a vital shock absorber during an external shock. Therefore, it could be said that banks should attach importance to income diversification, and sector regulators should encourage innovation to create non-traditional products. Under the adverse conjuncture created by increasing public intervention and the pandemic, in recent years, Turkish banks have been encouraged to diversify their activities further rather than focus solely on traditional activities. NNII appears to be associated with higher profitability and lower risk.